2013
DOI: 10.1109/tuffc.2013.6644747
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence: spatial variations of viscoelastic properties of porcine vitreous humors

Abstract: Using a microbubble-based acoustic radiation force approach, spatial variations of Young’s modulus and shear viscosity of the porcine vitreous humors in two groups— young pigs (6 months old) and mature pigs (2 to 3 years old)— were measured in situ. The measurements in these groups (4 specimens in each group) were performed in several positions along an anterior-to-posterior direction. At each position, microbubbles were generated by focusing a nanosecond pulsed laser beam and the displacement of each microbub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Other techniques for assessing vitreous elasticity include nuclear MRI for the liquefaction of the vitreous, 30 radiation force, 31 ultrasound image velocimetry, 32 and microbubble-based acoustic radiation force technique. 33 By using this last technique, Yoon et al 33 reported that the AV has a higher share of viscosity than the PV and central vitreous. Changes in the vitreous may be observed in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other techniques for assessing vitreous elasticity include nuclear MRI for the liquefaction of the vitreous, 30 radiation force, 31 ultrasound image velocimetry, 32 and microbubble-based acoustic radiation force technique. 33 By using this last technique, Yoon et al 33 reported that the AV has a higher share of viscosity than the PV and central vitreous. Changes in the vitreous may be observed in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the elastographic measurements were shown to have relatively lower elasticity values in PV in both the glaucomatous and healthy eyes ( Figure 1). Yoon et al 33 found that the viscosity of AV and PV are different. This supports our results.…”
Section: Discussionmentioning
confidence: 99%
“…While the vitreous humor is known to degrade with age, much less is known about its age-related changes in the mechanical properties of the vitreous humor, mostly due to the difficulty in obtaining human donor tissue at younger ages. Zimmerman (1980) reported the in vivo modulus of the vitreous from patients aged 18,26,28,38,47, and 50 years old and found no discernible differences due to age, potentially due to the unreliable measurements primarily based on patient compliance. 45 Weber et al (1982) calculated the spring constant and damping factor of human vitreous from donors aged 44 to 73 years but did not report any significant age-related changes.…”
Section: Aging Of the Vitreous Humormentioning
confidence: 99%
“…Ideally, the mechanical properties of the intact vitreous humor should be tested in vivo. Non-invasive techniques used to study the material properties of the vitreous include MRI, 12,19,30,36,42 light scattering, 35,45 microbubble-based acoustic radiation force 28 , ultrasound, 29,39,47 and Brillouin spectroscopy. 160 With the advantageous ability of nondestructive in vivo vitreous assessment, the disadvantage of these methods is that they do not provide data (storage modulus and loss modulus) that are comparable to the current rheological data on the vitreous humor or reported experimental hydrogel vitreous substitutes.…”
Section: The Need For In Vivo Measurements Of the Vitreous Humormentioning
confidence: 99%
“…Theoretical model of the motion of a solid sphere in a viscoelastic medium was developed and experimentally validated in our lab [21][22][23][24] . In our previous study, we developed a theoretical model of a gas bubble under ARF and measured the mechanical properties of the crystalline lens and the vitreous humor of bovine and porcine eyes using a 3 MHz transducer for pushing and a 25 MHz transducer for tracking [25][26][27][28] . In this study, we used a 130 MHz PUT to displace a solid sphere in a gelatin phantom and a 45 MHz tracking ultrasonic transducer (TUT) to track the displacement of the sphere.…”
mentioning
confidence: 99%